1995
DOI: 10.1042/bj3050239
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of cysteine-195 in isocitrate lyase from Escherichia coli ML308

Abstract: Cysteine-195 was previously identified as a probable active site residue in isocitrate lyase (ICL) from Escherichia coli ML308 [Nimmo, Douglas, Kleanthous, Campbell and MacKintosh (1989) Biochem. J. 261, 431-435]. This residue was replaced with serine and alanine residues by site-directed mutagenesis. The mutated genes expressed proteins with low but finite ICL activity, which co-migrated with wild-type ICL on both SDS/ and native PAGE. The mutant proteins were purified and characterized. Fluorimetry and c.d. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…This cysteine is strictly conserved in all known ICL, consistent with its crucial role in catalysis (29,30,50,51). This cysteine was proposed to be required for deprotonation of a carboxylate of succinate during the catalytic reaction (52).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This cysteine is strictly conserved in all known ICL, consistent with its crucial role in catalysis (29,30,50,51). This cysteine was proposed to be required for deprotonation of a carboxylate of succinate during the catalytic reaction (52).…”
Section: Discussionmentioning
confidence: 58%
“…1A). Cys 301 is only conserved in bacterial-type ICLs, whereas Cys 178 is conserved in all organisms, consistent with its role in catalysis (29,30) Because two cysteine residues of ICL have been previ-ously suggested to be sensitive to redox modifications (10,11,17), based on sequence conservation, Cys 178 and Cys 301 appear as the most likely candidates. Three-dimensional modeling of CrICL suggests that these two residues are the two closest cysteines in the enzyme but are too distant to allow formation of a disulfide bridge (Fig.…”
Section: Sequence and Phylogenetic Analysis Of Chlamydomonas Icl-mentioning
confidence: 81%
“…If the far UV and near UV CD spectra of the mutants are superimposable on those of the wild type protein, it can be concluded that the mutations have not resulted in any significant distortion of structure. This was found to be the case in two mutant forms of isocitrate lyase from Escherichia coli in which Cys 195 had been replaced by alanine or serine, leading to loss of activity [24] (see Fig. 2).…”
Section: Using Synchrotron Radiationmentioning
confidence: 88%
“…The far UV (a) and near UV (b) spectra for wild type enzyme and a mutant in which Cys 195 has been replaced by Ala are shown as solid and dashed lines respectively. The spectra of the mutant in which Cys 195 has been replaced by Ser are superimposable on those shown [24]. measurements in order to explore the relationships between quaternary and secondary or tertiary structures [26].…”
Section: Using Synchrotron Radiationmentioning
confidence: 99%
“…In Alg2p, highly conserved regions are revealed, such as the hexapeptides KKCGHM (ICL signature; Figure 2) and SPSFNW (active site signature; Figure 2). The former contains a Cys (Cys 213 ), homologous to S. cerevisiae Cys 195 and to E. coli Cys 217 , the significance of which has been discussed (Ko and McFadden, 1990; Rehman and McFadden, 1997; Robertson and Nimmo, 1995); the latter contains the sequence SPS, which is likely to take part in the formation of the enzyme–substrate bond (Ko et al , 1992). Towards the amino‐terminus (residues 32–40), this protein contains a short stretch (RLEGHQESL) rather similar to the consensus sequence for PTS2, one of the microbody (peroxisomal) targeting signals (see Subramani, 1998).…”
Section: Resultsmentioning
confidence: 99%